Ultrasensitive impedimetric immunosensor for the detection of C-reactive protein in blood at surface-initiated-reversible addition–fragmentation chain transfer generated poly(2-hydroxyethyl methacrylate) brushes - Kanyong, P; Catli, C; Davis, JJ (American Chemical Society, 2020)
The reversible addition–fragmentation chain transfer (RAFT) polymerization of 2-hydroxethyl methacrylate (HEMA) from a surface confined, dithio-tethered, chain transfer agent (CTA) enables the preparation of electrode-tethered poly(2-hydroxyethyl methacrylate) (pHEMA) brushes of well-defined thickness with convenience and exceptionally high interfacial impedimetric baseline stability. The subsequent covalent integration of antibodies generates interfaces of very high target recognition specificity, ultimately enabling femtomolar levels of quantification of C-reactive protein (CRP) and recovery in spiked serum samples of ∼98%. When combined with the intrinsic scalability of the reagentless electrochemical impedance spectroscopy (EIS) platform, and the innate high levels of polymer tuneability and control, we believe this represents a valuable contribution to the diagnostic toolbox.